PRELIMINARY ANALYSIS OF THE MACROBOTANICAL REMAINS FROM THE LATE ANTIQUE AND BYZANTINE PHASES OF THE DOMUS AT POMPEIOPOLIS - Tatbul, Mustafa; Gürdal, Tayyar; Tatbul, Mustafa Nuri (My University, 2022)
Archaeological excavations of the Domus complex at Pompeiopolis reveal significant information about the evolution of the settlement beginning from its foundation in the second half of the 3rd c., its transformation through the Late Antiquity - Early Byzantine – Transition Period (Dark Ages) and the Middle Byzantine phase of the complex before its abandonment sometime after the 11th-12th c. In the 2021 excavation season, 32 flotation samples were processed representing the multi-period occupation of the domestic complex. In this paper, macrobotanical materials recovered from the flotation samples are analyzed. The results are discussed in relation to the sample contexts representing different phases of the Domus. Özet: Pompeiopolis’te gerçekleştirilen arkeolojik kazılar Domus kompleksinin 3. yüzyılın ikinci yarısında inşa edilmesinden, 11.-12. yüzyılın sonrasında terkedilmesine kadar geçen zaman içinde Geç Antik Çağ – Erken Bizans – Geçiş Dönemi (Karanlık Çağ) ve Orta Bizans dönemlerindeki dönüşümü hakkında önemli bilgiler sunmaktadır. 2021 kazı sezonunda bu konutsal alanın çok dönemli iskanını temsil eden 32 flotasyon örneği incelenmiştir. Bu makalede flotasyon örneklerinden ayrıştırılmış olan makrobotanik kalıntılar analiz edilmiş, Domus kompleksinin farklı dönemlerini temsil eden örneklerden elde edilen sonuçlar bağlamlarıyla ilişkili olarak tartışılmıştır.
Keywords: Arkeoloji; Tarih; Black Sea; Archaeobotany; Contextual interpretation; Domestic; Late Antique and Byzantine Archaeology; Medieval Anatolia